Cardiovascular Risk Categories in Patients With Nonalcoholic Fatty Liver Disease and the Role of Low‐Density Lipoprotein Cholesterol. Issue 11 (30th September 2019) - Labenz, Christian; Prochaska, Jürgen H.; Huber, Yvonne; Nagel, Michael; Straub, Beate K.; Wild, Philipp; Galle, Peter R.; Schattenberg, Jörn M.
Abstract : Cardiovascular disease (CVD) is the leading cause of death in patients with nonalcoholic fatty liver disease (NAFLD). The current analysis expands the knowledge on atherogenic lipid profiles in NAFLD by modeling changes in low‐density lipoprotein cholesterol (LDL‐C) and total cholesterol (TC) in a prospectively enrolling real‐life study cohort to inform physicians on the cardiovascular (CV) event risk based on these changes. A total of 304 patients with histologically confirmed NAFLD were included (mean age, 52 years; equal sex distribution). Of these, 129 (42.4%) patients exhibited a NAFLD activity score ≥4 and 186 (61.2%) had at least intermediate fibrosis ≥F2. The median TC levels were 209 mg/dL (interquartile range [IQR], 183, 239), LDL‐C 131 mg/dL (IQR, 103, 152), and high‐density lipoprotein cholesterol (HDL‐C) 45 mg/dL (IQR, 38, 52). Only 16.9% of patients received lipid‐lowering therapy. According to the LDL/HDL ratio, 69 (23.7%) patients exhibited a high CV risk. The 10‐year CV event risk according to the Framingham risk score (FRS) was low in 91 (41.2%), intermediate in 59 (26.7%), and high in 71 (32.1%) patients and higher in the ≥F2 NAFLD population. A moderate increase in LDL‐C levels by 20 mg/dL led to a transition of 20% of patients into the high‐risk group when assessing the LDL/HDL ratio. According to the FRS, 6 (2.7%) patients moved from low to intermediate and 11 (4.9%) from intermediate to high CV risk. Conclusion : Patients with NAFLD exhibit a substantial CV event risk and are frequently undertreated with lipid‐lowering medication. Moderate increases in LDL‐C would result in worsening of the CV event risk in approximately 7.8% of all patients without a history of CVD. Abstract : NAFLD patients exhibit an increased cardiovascular mortality. Assessment of the cardiovascular event risk will help clinicians to manage these patients. The current analysis provides real‐world evidence in a cohort of biopsy‐proven NAFLD patients and segregates high and low risk categories for incident CVD disease. This data will support in the decision on pharmacotherapy and in particular NASH‐directed therapies in the future.